INTERNASIONALISASI BAHASA INDONESIA MELALUI EKSPOSE VISUAL CERITA DAERAH MENGGUNAKAN KOMIK DIGITAL BILINGUAL - Umaya, Nazla Maharani (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura)
This article discusses the use of digital comics as a medium of Indonesian language internationalization. Some things that are part of the study are the analysis of global Indonesian digital comics, the opportunity for space in developing digital comics as a medium of massive communication between language and language users, the use of regional wealth in Indonesia as a bearer of Identity, and visual exposure of regional stories as strategies Internationalization of Indonesian. The method of analysis uses exploratory studies with literature reviews, aimed at exploring digital world space and opportunities for the internationalization of Indonesian through the use of a wealth of language, literature and culture. The benefits of this are providing a basic foothold in supporting further research on the potential of literary and cultural languages in internationalizing Indonesian. The use of digital technology that is becoming popular has become a great opportunity for the development of various strategies. The results of the study in the form of key points as a key application of the strategy of internationalization of Indonesian by utilizing the local wealth of the work of the Indonesian people conceptually.